Acceptance of a Proposed Model Based on Using Web 2.0 for Developing English Writing Skills - Al-Sufyani, Dalal; Al-Sofyani, Mohammed (European Scientific Journal, ESJ, 2016)
The study aimed at designing a proposed model for developing English writing skills using web 2.0 tools and exploring its acceptance level from students' and instructors' perspectives. The study adopted the descriptive methodology. Eight female instructors responded to the instructors' questionnaire. Also, twenty female students responded to the students' questionnaire. To analyse the quantitative data, the means of participants' respondents were calculated. The most important results were both students and instructors who participated in the current study accepted the proposed model. Based on the results of the study, the most important recommendations were: using technology, especially the proposed model in teaching at ELC.